Implementasi Budaya Kerja Dalam Meningkatkan Layanan Pada Bagian Tata Usaha - Hafshah Saidah Rusli; Abdul Kosim; Kasja Eki Waluyo (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research was conducted based on the problems found, namely, the application of work culture in improving administrative services that were deemed less than optimal. The purpose of this study was to determine how the implementation of work culture in Man 2 Karawang, and to find out the supporting and inhibiting factors in implementing it. By using a descriptive qualitative approach and data collection techniques through interviews, observation, and documentation. The results of the research carried out, that in its application the work culture has been socialized by the madrasa principal as a whole, it can be seen by the regulations made to come according to working hours, do their duties and responsibilities well, be friendly with employees or with students and parents. This shows that as an administrative employee, he has carried out quite well, it's just that not everything is embedded in himself. As for the inhibiting factors that occur such as the presence of employees who arrive late, in a hurry so that they are not prepared to provide good service. While the supporting factor is the motivation given through the head of administration or directly by the head of the madrasa and giving rewards to employees